Involvement of non‐melanocytic skin cells in vitiligo. Issue 6 (11th February 2019) - Bastonini, Emanuela; Bellei, Barbara; Filoni, Angela; Kovacs, Daniela; Iacovelli, Paolo; Picardo, Mauro
Abstract: Despite melanocytes are the key players in vitiligo, a continuous cross‐talk between epidermal and dermal cells may strictly affect their functionality, in both lesional skin and non‐lesional skin. Focusing on this interplay, we have reviewed existing literature supporting evidence on cellular and functional alterations of surrounding epidermal keratinocytes, extracellular matrix (ECM) proteins and fibroblasts in the underlying dermal compartment that may contribute to melanocyte disappearance in vitiligo. We have also examined some clinical and therapeutic aspects of the disease to sustain the non‐exclusive involvement of melanocytes within vitiligo. As a result, a different and more complex scenario has appeared that may enable to provide better understanding about origins and progress of vitiligo and that should be considered in the evaluation of new treatment approaches.